IDENTIFIKASI PELAKU KECURANGAN DENGAN MENGGUNAKAN POLINOMIAL BIVARIAT SIMETRIS: Universitas Timor - Aprilia Lopo; Zulkaidah Nur Ahzan; Fitriani Fitriani; Nugraha K. F. Dethan (Program Studi Matematika, Universitas Timor, 2025)
The purpose of this study is to identify fraudsters using Symmetric Bivariate Polynomials with one share detecion. This type of research is quantitative using the method Secret Sharing Scheme (SPR). Where in this study combines several schemes, one of which is Scheme Liu et al. (2018). The scheme Liu et al. (2018) is a Symmetric Bivariate Polynomial scheme, in the writing of the Liu et al. (2018) scheme they identy fraudsters using two share detections. In the study, researchers also use Symmetric Bivariate Polynomials to identify fraudsters, so that the results are obtained, namely at the secret shering stage using Symmetric Bivariate Polynomials, at the reconstruction stage using Lagrange interpolation and using Symmetric Bivariate Polynimials with one share detection where is a random integer. Thus it can be concluded that the identification of fraudsters using Symmetric Bivariate Polynimoials is able to identify fraudsters and by using one share detection is faster in the computation process.